The Pleistocene Glyptodontidae Gray, 1869 (Xenarthra: Cingulata) of Colombia and some considerations about the South American Glyptodontinae - Zurita, Alfredo Eduardo (2012)
Until recently, one well-characterized Pleistocene genus of the subfamily Glyptodontinae (Glyptodon ca. 1.08-0.0011 My) was recognized in South America. In recent times, some authors have demonstrated, through the re-analysis of material originally classified as Glyptodon Owen and Hoplophorus Lund, the presence of a second species belonging to the North American glyptodontine Glyptotherium Osborn (ca. 58-12 ky BP), currently known from in Venezuela and Brazil. This situation implies the need for a new study, with modern taxonomical criteria, of those materials belonging to the Glyptodontinae, particularly in those territories where the knowledge of these taxa is scarce. Presented here is a new analysis of the Pleistocene Glyptodontidae from Colombia, including some taxonomic and paleobiogeographic remarks. The results show that the only reported Glyptodontidae specimens in Colombia belong to Glyptodon sp. In turn, the evidence suggests that only one single species of Glyptotherium is present in South America, currently assigned to Glyptotherium cf. Gl. cylindricum. However, a more accurate analysis is necessary to confirm or refute this taxonomic identification. To date, Glyptotherium present has been found only in an area parallel to the Caribbean Sea and the Atlantic Ocean (northern Venezuela and eastern Brazil), up to 20°S, and is always linked to lowlands. This geographic distribution agrees with the proposition of an eastern corridor during the Great American Biotic Interchange. Below this latitude, the only recorded glyptodontine corresponds to Glyptodon, which is also recorded in a strip parallel to the Cordillera de Los Andes reaching Colombia and Venezuela. Taking into account this distribution, the presence of this genus in Central America cannot be discarded.